The integration of a problem-solving framework for Brunei high school mathematics curriculum in increasing student’s affective competency - Chong, Maureen Siew Fang; Shahrill, Masitah; Li, Hui-Chuan (Journal on Mathematics Education, 2019)
A mathematics framework was developed to integrate problem-solving that incorporated simulation of real-life problems in the classrooms. The framework coined as the RECCE-MODEL emphasised understanding and thinking with a view on mathematics embedded in real-life. The RECCE which stands for Realistic, Educational, Contextual, Cognitive, and Evaluation encompass the underlying principles of teaching problem solving and guide teachers in planning, designing, developing, and facilitating real-life activity tasks in developing students’ problem-solving competencies in mathematics lessons. It also explores students’ cognitive competency in their application of abstract mathematical knowledge into real-life problems based on students’ developmental status of their thinking and reasoning skills correlating to Meanings, Organise, Develop, Execute and Link (MODEL). This study investigated the affective development of the students through activity tasks developed by the sampled teachers using the principles within the framework. In total, 94 students from two high schools in Brunei Darussalam responded to a students’ questionnaire constructed to address the MODEL aspect of the framework. In particular, the analyses involved the students’ affective competencies that corresponded to a 19-item instrument within the questionnaire. The findings showed that Brunei high school students have stimulated beliefs and positive attitudes towards non-routine problem-solving in the learning of mathematics. Meanwhile, meaningful activities developed by the teachers encouraged the development of cognitive-metacognitive and affective competencies of the students. The RECCE-MODEL framework paved the way towards understanding the relationships between effective pedagogical approaches and students’ learning, and between attitudes and cognitive abilities, and also for teachers to make better-informed decisions in the delivery of the curriculum.